2022
DOI: 10.36341/psi.v6i1.2554
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategy dengan Parenting Stress pada Polwan yang Memiliki Balita

Abstract: Parenting stress merupakan keadaan dan perasaan negatif yang dialami orang tua terhadap tuntutan peran pengasuhan, Parenting stress dipengaruhi salah satu faktor yaitu kemampuan internal, faktor ini berkaitan dengan kemampuan seorang ibu menggunakan coping strategy untuk mengatasi stres mengasuh anak. Tujuannya untuk melihat apakah ada hubungan coping strategy dengan parenting stress pada Polwan Polresta Pekanbaru. Penelitian menggunakan metode kuantitatif dengan analisis regresi linear berganda. Subjek peneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…The findings of this study also show a significant positive influence between problem-focused coping and the quality of the parenting environment. In line with Lestari et al (2022) who found that problem-focused coping has a significant effect on parenting stress. The application of problem-focused coping focuses on direct resolution, practical help, and information to overcome the problems faced.…”
Section: Discussionsupporting
confidence: 75%
“…The findings of this study also show a significant positive influence between problem-focused coping and the quality of the parenting environment. In line with Lestari et al (2022) who found that problem-focused coping has a significant effect on parenting stress. The application of problem-focused coping focuses on direct resolution, practical help, and information to overcome the problems faced.…”
Section: Discussionsupporting
confidence: 75%